The road to monetary union in Latin America: An EMS-type fixed exchange rate system as an intermediate step - Daniel Garcia Rocabado (University of Würzburg, Department of Economics, 2010)
In the light of new political initiatives in Latin America, discussions of expanding the monetary cooperation in the region have intensified and the idea of monetary union is gaining popularity. Since literature on the subject widely dismisses the feasibility of Latin America adopting a single currency in the short- to medium-term, several authors have proposed to follow the European example by establishing a regional exchange rate system, similar to the European Monetary System (EMS), as an intermediate step. While these proposals usually describe the general benefits of an EMS-type system for Latin America, they rarely discuss how such a regional arrangement can institutionally be designed or what the main lessons are, that can be derived from the EMS experience, in order for a Latin American exchange rate system to be successful. Thus, it is the central aim of this paper to address these specific issues by providing a detailed look at the design and functioning of regional fixed rate systems as an intermediate step towards monetary union. For this purpose, first, an overview of the current Latin American initiatives in the field of monetary integration is given, followed by a general analysis of fixed rate systems from an institutional perspective. This analysis presents the basic design choices available to policymakers when creating such a system and describes how the decided upon rules (i.e. the institutional framework) determine the overall monetary adjustment constraints for the participating countries. Further, the paper examines the historic, political and economic rationale as well as the overall institutional design and functioning of a specific fixed rate system, namely the EMS. It is shown that the EMS did not only constitute an efficient monetary arrangement by effectively reducing both nominal and real exchange rate variability in the region, but can also be considered a successful intermediate step towards monetary union in Europe. The paper ends with a discussion of the main lessons drawn from the EMS analysis and their implications for the Latin American prospects of possibly establishing a similar regional exchange rate mechanism.
Keywords: F31; F33; F55; 330; Latin American Integration; Monetary Cooperation; fixed exchange rates; European Monetary System